Nationalism and the Reshaping of Urban Communities in Europe, 1848-1914
XI, 324 p.
Keywords: This book brings together a distinguished group of historians to explore the previously neglected relationship between nationalism and urban history. It reveals the contrasting experiences of nationalism in different societies and milieus. It will help historians to reassess the role of nationalism both inside and outside the nation state.